Improving recovery of hybrid rocking walls through locally heat-treated replaceable bars for hysteretic energy dissipation. (15th September 2022) - Kalliontzis, Dimitrios; Morrison, Machel; Liu, Qingzhi; Nazari, Maryam; Kotzamanis, Vasileios
Highlights: Hybrid rocking wall (HRW) systems have been shown to behave satisfactorily under lateral seismic loads. However, inspection and replacement of the energy dissipating bars used in HRWs may not be economically achieved after earthquake events. This paper presents a new design concept for HRWs utilizing a localized heat treatment methodology to concentrate hysteretic action in replaceable segments of the bars. The proposed HRW system was examined analytically in this paper and detailing recommendations for the energy dissipating bars were developed. Abstract: Rocking walls continue to gain interest in seismic regions due to their ability of re-centering the building system after major earthquakes. However, they have low inherent damping, thus they are often supplemented with energy dissipating elements. A rocking wall supplemented with partially debonded longitudinal bars is named as a hybrid rocking wall (HRW). While HRWs combine re-centering with adequate energy dissipation, inspection and replacement of the energy dissipating bars may not be economically achieved after a major earthquake. This paper proposes an improvement to HRWs with the use of partially debonded longitudinal bars that are locally heat-treated to strategically concentrate hysteretic action in replaceable bar segments. The effect of the heat treatment protocol on the stress-strain properties and microstructure of reinforcing bars is investigated experimentally and a procedure for locally heat-treating standard reinforcing bars is established. Combining the experimental data of heat treatment with an analytical model for HRWs, the reversed-cyclic behavior of the proposed HRW is investigated to characterize the energy dissipation through the heat-treated bar segments, the re-centering capability of the HRW, and other key design parameters of the proposed wall system.